INCREASING INTENSIVE STUDY BY USING COMBINATION MODEL OF THE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC), TEAM ASSISTED INDIVIDUALIZATION (TAI), AND NUMBERED HEAD TOGETHER (NHT) - Azizah, Azizah; Ramadi, Ramadi; Noviyanti, Noviyanti (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2018)
The purpose of this study is to determine the activities of the teacher, student activities and student learning outcomes read intensive through the combination of learning models Cooperative Integrated Reading and Composition (CIRC), Team Assisted Individualization (TAI) and the Numbered Head Together (NHT). This research is using class behavior research which is done in 2 cycles. Research setting is in the SDN Pengambangan 9 East Banjarmasin school year 2016/2017 2nd semester in grade IV. The results showed that there is an increase in each cycle. It can be seen from the teacher's activity in the cycle that earned the score 33 with category